(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In almost every field, huge amount of data is available. Big Data is that field of database management system that has been used for data collection. Millions of records have been stored on the big data servers that are indexed properly. The relation between various data instances has been built so that access to the particular data must be easy. Due to large amount of data big, there are many challenges in handling it. These challenges are scalability, availability, security and confidentiality. In this paper various challenges and issues has been discussed that cause various problems in utilization of big data concept.